Metallic antimony recovery via cementation from antimony containing solutions and investigation of its conditions - ÇETİNER, BURCU NİLGÜN; AKTAŞ, SERDAR (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
Besides the most common uses of antimony metal and / or compounds, with the development of solar energy technologies, the need for antimony and its compounds increases and the rapid depletion of primary sources in the world increases the importance of antimony recovery from secondary sources. The recovery method proposed in this study aims to reduce the ionic antimony by oxidation of the more active metal and to produce metallic antimony in powder form as a result of reduction process. Oxide based antimony containing ore has been treated by acidic solutions. But as the recovery rate was too low, the parameters affecting the metallic precipitation of antimony from acidic synthetic antimony solutions which are a secondary source were examined in detail. The physical and chemical properties of antimony metal were determined after examining reaction time, temperature, initial antimony concentration, zinc powder amount and solution pH parameters during cementation process which could affect experimental working conditions. As a result of the experimental studies, using 25 mL of 1000 ppm Sb3(+) synthetic solution with the addition of 100 mg of metallic zinc and mixing speed of 60 rpm, recovery efficiency of up to 100% was achieved in a noticeably short time such as 5 minutes and metallic antimony of 99% purity was obtained. When 100% recovery was achieved with zinc of 100 mg in single-stage cementation, the same yield was achieved with the addition of 40% less zinc in two-stage cementation.
Keywords: Cementation; zinc; metallic antimony; WASTE-WATER; COBALT CEMENTATION; ZINC; COPPER; REMOVAL; OPTIMIZATION; LEAD